Brominated Diphenyl Ethers Including a New Tribromoiododiphenyl Ether from the Vietnamese Marine Sponge Arenosclera sp. and Their Antibacterial Activities. Issue 3 (8th February 2019) - Ki, Dae‐Won; Awouafack, Maurice Ducret; Wong, Chin Piow; Nguyen, Hien Minh; Thai, Quang Minh; Ton Nu, Lien Huong; Morita, Hiroyuki
Abstract: A new tribromoiododiphenyl ether (1 ) and eight known brominated diphenyl ethers (2 –9 ) were isolated from the MeOH extract of the sponge Arenosclera sp. collected in Vietnam, using repeated open column chromatography and preparative thin layer chromatography. The chemical structure of the new compound1 was determined by analyses of spectroscopic (1D‐ and 2D‐NMR, and MS) data and by comparison of our data with those reported in the literature. Compounds1, 3, and8 exhibited strong antibacterial activities against the Gram‐positive bacteria Bacillus subtilis and Staphylococcus aureus and the Gram‐negative bacterium Klebsiella pneumoniae with MIC values ranging from 0.8 to 6.3 μm, while compounds5 and7 only displayed activities against Gram‐positive bacteria with MIC values from 0.5 to 3.1 μm . Compound2 showed activities against the four tested bacteria with MIC values ranging from 0.5 to 6.3 μm . Abstract :